UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM OPERASI PERKALIAN MATERI BILANGAN DENGAN METODE LATTICE DI KELAS V SDN DUKUH KUPANG 1 SURABAYA - Afriska Amelia Herwinsyah Putri; Mintohari; Kriswati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to improve student learning outcomes in multiplication operations involving whole numbers and decimals by using the lattice method in Grade V at SDN Dukuh Kupang 1-488 Surabaya. The lattice method was chosen because it offers a systematic approach to solving multiplication problems, which students often find difficult. The research was conducted through classroom action research (CAR) over two cycles, involving 31 students. Each cycle consisted of planning, implementation, observation, and reflection. Data were collected through tests, observations, and interviews. The results showed that in the first cycle, the students' average score was 67.50, with a mastery learning percentage of 58.06%. After improvements in the second cycle, the average score increased to 80.30, with a mastery percentage of 80.65%. This improvement in learning outcomes indicates the effectiveness of the lattice method in helping students understand multiplication concepts. Additionally, this method also increased students' motivation and confidence in learning mathematics. However, some challenges were encountered during the implementation of the lattice method, such as the time students needed to adapt and the lack of variety in practice problems. This study suggests that the lattice method should be introduced early on to help students grasp multiplication operations more easily, and that teachers should engage in regular reflection to enhance the quality of instruction. Overall, the lattice method has proven effective in improving student learning outcomes, especially in multiplication of whole numbers and decimals.